Diseño y fortalecimiento del área comercial de la empresa Triángulo del Café S.A.S Armenia – Quindío (2016)
This analitycal investigation was carried out structure the implementation of the commercial area of the company, due to new business oportunities and challenges we have to plan and implement the conformation of the area of the company CIA. Triangulo Del Café S.A.S to fulfill this objective, i conduct a qualitative research along with a with descriptive design, using the interview as the form of data collection technique including both external and internal factors. Subjects used as internal sample were eight education instructors working in the company for a period of at least ten months. Subjects used as external sample were 20 companies with which it had a contract with a company for at least 3 months located in the department of Quindío. According to the results obtained it was evident the need to design a and implement the commercial area of the company. This include the need to strengthen the structure of internal processes according to the market needs, also improve the conditions of human and physical resources for increased performance and a better customer service. Purpose, Commercial Area, Growth, Market, Design, Services, Organizational Structure, Business, Business, Process, Compliance, Research, descriptive, survey, Need, Resources, External factors, internal factors, strengthening, Improvement, Service.